A Method for Improving the Prevention of Dental Caries in Children Using the Device Aerodent - Raхmatova Dilnora Saidjonovna (Academia One, 2024)
Dental caries is the most common chronic disease among the child population. Caries of milk teeth occupies a special place in the structure of this pathology. Despite the improvement in the quality and expansion of the volume of preventive and therapeutic measures, the level of intensity and severity of early childhood caries in our country and the Perm region in particular remains at a very high level. There are more than a hundred reasons contributing to the development of carious process in milk teeth. Of these, the most important are socio-demographic, biological, dietary, hygienic and factors related to the type of feeding. In this case, the consolidation or weakening of the action of such in a number of circumstances will determine the emergence and further development of early childhood caries. In the classical sense, dental caries is a chronic infectious disease induced by a violation of diet.
Keywords: Dental caries; physiological; multifactorial polyetiological disease